A chopper amplifier with adaptive biasing OTA for biomedical applications, featuring high gain and CMRR. - Bhaskara Rao Kasipogula; Gurumurthy Komanapalli (PLoS ONE)
This paper presents a design of fully differential chopper amplifier employing the flipped voltage follower (FVF) adaptive biasing technique, focusing on its potential use in biopotential recording applications. The suggested architectural OTA incorporates self-cascoded current mirrors (SCCMs) as the active load to achieve a substantial output swing. The FVFs based adaptive biasing approach for the differential input stage boosts extra current and enhances gain and dynamic characteristics. The chopper amplifier attains a common mode rejection ratio (CMRR) of more than 100 dB through the strategic utilization of chopper modulators and pseudo-resistors. Additionally, this device exhibits characteristics such as accurate and stable gain, high input impedance, and a compact physical footprint. The present study also includes a comparison between the suggested structure and the bio-potential amplifiers discussed in the existing literature. This comparison is based on key metrics such as gain, input referred noise (IRN), CMRR, and input impedance (Zin). The proposed structure yielded a gain of 63.72 dB, an IRN of 0.07nVrms, a CMRR of 127.97 dB and a Zin of 1.54 GΩ. The bio-potential chopper amplifier under consideration was constructed and simulations were performed by utilizing the Cadence Virtuoso Spectre simulator tool at 180 nm CMOS technology node.